Contemporary woman in the context of motherhood and the role of a mother - Krause, Ewa (EDUsfera. Ewa Jurczyk-Romanowska, 2020)
The responsibilities of a contemporary woman are increasing, and the repertoire of new roles is constantly expanding. However, the role of the mother is particularly marked, and burdened with a „social response”. Motherhood is the subject of analysis by many researchers. Most often it remains in the area of interest of demographers, psychologists, sociologists, and pedagogists. This topic is considered to be constantly relevant, popular both in the scientific discourse and in social discussion. Therefore, it is important to constantly explore this issue; they also reveal new contexts – in this case, the situation of mothers during the Covid-19 pandemic was referred to
Keywords: motherhood; mother role; social perception; categories/”types” of contemporary women; the Covid-19 pandemic